Positive electrode slurry and preparation method thereof, positive electrode plate, secondary battery, battery module, battery pack and electric device

CN119731807AActive Publication Date: 2025-03-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280008928.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-14
Publication Date
2025-03-28
Estimated Expiration
2042-07-14

AI Technical Summary

Technical Problem

In the traditional lithium-ion battery preparation process, the N-methylpyrrolidone (NMP)-polyvinylidene fluoride (PVDF) system oily cathode slurry used in the cathode plate has problems of difficulty in recycling, high cost and environmental pollution, and iron phosphate Cathode active materials such as lithium tend to deteriorate when exposed to water.

Method used

Aqueous cathode slurry containing lithium graphene is used. Lithium graphene coats the cathode active material through π-π stacking to form a hydrophilic layer, which improves dispersion and reduces the risk of water absorption. Combined with an appropriate amount of dispersant and water-based binder, A positive electrode piece with good processability and low cost is prepared.

Benefits of technology

It effectively avoids the deterioration of the performance of the cathode active material, improves the lithium ion transmission performance, reduces the preparation cost, is environmentally friendly, and improves the kinetic performance and dispersion of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731807A_ABST
    Figure CN119731807A_ABST
Patent Text Reader

Abstract

The invention provides positive electrode slurry. The positive electrode slurry comprises solids and water, the solid content comprises a positive electrode active material capable of intercalating and deintercalating lithium ions and lithium-containing graphene.
Need to check novelty before this filing date? Find Prior Art

Description

Positive electrode slurry and preparation method thereof, positive electrode sheet, secondary battery, battery module, battery pack and electrical device Technical Field

[0001] The present application relates to the field of secondary batteries, and specifically to a positive electrode slurry and a preparation method thereof, a positive electrode sheet, a secondary battery, a battery module, a battery pack and an electrical device. Background Art

[0002] Lithium-ion batteries and other secondary batteries are widely used in consumer electronics, electric vehicles, and other fields due to their advantages such as high energy density, excellent cycle performance, and high average output voltage. Because cathode active materials such as lithium iron phosphate (LiFePO4) are susceptible to deterioration upon contact with water, traditional Li-ion battery manufacturing processes typically use an oily cathode slurry composed of N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF). However, NMP solvents present challenges such as difficulty in recycling, high cost, and environmental pollution.

[0003] Summary of the Invention

[0004] Based on the above problems, the present application provides a positive electrode slurry and its preparation method, a positive electrode sheet, a secondary battery, a battery module, a battery pack and an electrical device, which can effectively prevent the deterioration of the positive electrode active material, and has good processability and low cost.

[0005] In one aspect of the present application, a positive electrode slurry is provided, comprising a solid content and water;

[0006] The solid content includes a positive electrode active material capable of inserting and extracting lithium ions and lithium-containing graphene.

[0007] The positive electrode slurry of the present application, due to the π-π stacking effect of lithium-containing graphene, in the positive electrode slurry, the lithium-containing graphene can coat the positive electrode active material, thereby preventing the positive electrode active material from binding with water and causing performance deterioration; at the same time, the solid content has good dispersibility in solvent water, has good processability, low cost, and is environmentally friendly.

[0008] In some embodiments, the lithium-containing graphene is at least partially coated on the surface of the positive electrode active material. This at least partially coating of the lithium-containing graphene on the surface of the positive electrode active material can form a hydrophilic layer on the surface of the positive electrode active material, improving the dispersibility of the positive electrode active material while preventing the positive electrode active material from contacting water. Furthermore, the lithium ions in the lithium-containing graphene can also improve lithium ion transport within the positive electrode sheet, resulting in better kinetic performance of the secondary battery.

[0009] In some embodiments, the lithium-containing graphene includes lithium sulfonate-containing graphene. The sulfonic acid groups in the lithium sulfonate-containing graphene can further improve the dispersibility of the positive electrode active material in the positive electrode slurry through electrostatic repulsion, thereby improving the processability of the positive electrode slurry.

[0010] In some embodiments, the molar ratio of Li to S in the lithium sulfonate-containing graphene is 1:(1-10); alternatively, the molar ratio of Li to S in the lithium sulfonate-containing graphene is 1:(1-5). When the molar ratio of Li to S in the lithium sulfonate-containing graphene is within the above range, the secondary battery prepared with the positive electrode slurry has better kinetic performance.

[0011] In some embodiments, the molar ratio of C element to S element in the lithium sulfonate-containing graphene is (3-12):1.

[0012] In some embodiments, the weight percentage of the lithium-containing graphene in the solid content is 0.01% to 2%; alternatively, the weight percentage of the lithium-containing graphene in the solid content is 0.2% to 1.5%. The weight percentage of the lithium-containing graphene within the above range can effectively improve the dispersibility of the positive electrode active material in the aqueous positive electrode slurry and prevent the positive electrode active material from deteriorating due to water absorption.

[0013] In some embodiments, the positive electrode active material includes LiFe m Mn 1-m PO4、Li(Ni x Co y Mn z Al a Cu b Zn c Ti d ) at least one of O2, 0≤m≤1, x+y+z+a+b+c+d=1, 0.5≤x<1, 0.05≤y<1, 0≤z<0.5, 0≤a≤0.1, 0≤b≤0.1, 0≤c≤0.1, 0≤d≤0.1;

[0014] Optionally, the positive electrode active material is LiFePO4.

[0015] In some embodiments, the solid content further includes a dispersant. Optionally, the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant. Optionally, the dispersant includes at least one of polyethyleneimine and polyethylene glycol octylphenyl ether. These dispersants act synergistically with the lithium-containing graphene to further improve the dispersibility of the positive electrode slurry.

[0016] In some embodiments, the mass percentage of the dispersant in the solid content is 0.01% to 2%; alternatively, the mass percentage of the dispersant in the solid content is 0.1% to 0.5%. When the mass percentage of the dispersant is within the above range, the positive electrode slurry has good dispersibility and good processing performance.

[0017] In some embodiments, the solid content further includes an aqueous binder; optionally, the aqueous binder includes at least one of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, and acrylonitrile-acrylic acid copolymer and its derivatives. The aqueous binder is soluble in water, and the positive electrode slurry has suitable viscosity and adhesiveness.

[0018] In some embodiments, the aqueous binder is an acrylonitrile-acrylic acid copolymer; optionally, the acrylonitrile-acrylic acid copolymer has a number average molecular weight of 300,000 to 2,000,000.

[0019] In some embodiments, the mass percentage of the aqueous binder in the solid content is 0.1% to 5%; alternatively, the mass percentage of the aqueous binder in the solid content is 2% to 4%. When the mass percentage of the aqueous binder is within the above range, the positive electrode slurry has a relatively suitable viscosity, which is conducive to the preparation of positive electrode sheets.

[0020] In some embodiments, the solid content further includes a conductive agent; optionally, the conductive agent includes at least one of conductive carbon black, superconducting carbon black, conductive graphite, acetylene black, Ketjen black, graphene and carbon nanotubes.

[0021] In some embodiments, the mass percentage of the conductive agent in the solid content is 0.1% to 5%; optionally, the mass percentage of the conductive agent in the solid content is 0.5% to 3%.

[0022] In some embodiments, the solid content in the positive electrode slurry is 40% to 90% by weight; alternatively, the solid content in the positive electrode slurry is 50% to 70% by weight. The solid content in the positive electrode slurry has good dispersibility, and the solid content can reach 90% by weight, further reducing the amount of solvent water used.

[0023] In some embodiments, the viscosity of the positive electrode slurry is 100 cp to 10,000 cp; alternatively, the viscosity of the positive electrode slurry is 3,000 cp to 7,000 cp. The viscosity of the positive electrode slurry within the above range is conducive to subsequent processing and preparation of positive electrode sheets.

[0024] In a second aspect, the present application also provides a method for preparing the above-mentioned positive electrode slurry, comprising the following steps:

[0025] The solid content and the water are mixed.

[0026] In some embodiments, the step of mixing the solids and water comprises:

[0027] Mixing the positive electrode active material, lithium-containing graphene, a dispersant, and a conductive agent to prepare a pelletized material;

[0028] The dough material, aqueous binder and water are mixed.

[0029] First, the positive electrode active material, lithium-containing graphene and dispersant are mixed to prepare a mass material, which can further improve the dispersibility of the positive electrode active material in the positive electrode slurry and avoid agglomeration or gelation.

[0030] In a third aspect, the present application further provides a positive electrode sheet, comprising:

[0031] positive electrode current collector; and

[0032] A positive electrode active material layer is provided on at least one surface of the positive electrode current collector; the positive electrode active material layer is prepared according to the positive electrode slurry.

[0033] In some embodiments, the positive electrode active material layer includes lithium sulfonate-containing graphene; optionally, in the positive electrode active material layer, the molar ratio of Li element to S element is (10-5000):1.

[0034] In a fourth aspect, the present application further provides a method for preparing a positive electrode sheet, comprising the following steps:

[0035] A positive electrode active material layer is prepared on at least one surface of a positive electrode current collector using a positive electrode slurry; the positive electrode slurry uses the positive electrode slurry mentioned above.

[0036] In a fifth aspect, the present application also provides a secondary battery, comprising the above-mentioned positive electrode sheet or a positive electrode sheet prepared according to the above-mentioned method for preparing the positive electrode sheet.

[0037] In a sixth aspect, the present application also provides a battery module, comprising the above-mentioned secondary battery.

[0038] In a seventh aspect, the present application also provides a battery pack comprising the above-mentioned battery module.

[0039] In an eighth aspect, the present application further provides an electrical device comprising at least one selected from the above-mentioned secondary battery, the above-mentioned battery module and the above-mentioned battery pack.

[0040] The details of one or more embodiments of the present application are set forth in the accompanying drawings and the description below, and other features, objects, and advantages of the present application will be apparent from the description, the drawings, and the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0042] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;

[0043] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0044] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0045] FIG5 is an exploded view of the battery pack shown in FIG4 according to an embodiment of the present application;

[0046] FIG6 is a schematic diagram of an electrical device using a secondary battery as a power source according to an embodiment of the present application;

[0047] Description of reference numerals:

[0048] 1. Battery pack; 2. Upper case; 3. Lower case; 4. Battery module; 5. Secondary battery; 5. Casing; 5. Electrode assembly; 5. Cover; 6. Electrical device.

[0049] In order to better describe and illustrate the embodiments and / or examples of the inventions disclosed herein, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered to limit the scope of the disclosed inventions, the presently described embodiments and / or examples, and any of the best modes currently understood for these inventions. DETAILED DESCRIPTION

[0050] To facilitate understanding of the present application, a more comprehensive description of the present application will be provided below with reference to the accompanying drawings. The accompanying drawings illustrate preferred embodiments of the present application. However, the present application may be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and comprehensive understanding of the disclosure of the present application.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application pertains. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0052] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0055] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0056] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0057] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0058] The present application provides a positive electrode slurry and a preparation method thereof, as well as a positive electrode sheet, a secondary battery, a battery module, a battery pack, and an electrical device prepared using the positive electrode slurry. The secondary battery is suitable for various electrical devices using batteries, such as mobile phones, portable devices, laptop computers, electric vehicles, electric toys, electric tools, electric vehicles, ships, and spacecraft, such as aircraft, rockets, space shuttles, and spacecraft.

[0059] One embodiment of the present application provides a positive electrode slurry comprising a solid content and water, wherein the solid content comprises a positive electrode active material capable of inserting and extracting lithium ions and lithium-containing graphene.

[0060] The positive electrode slurry of the present application, due to the π-π stacking effect of lithium-containing graphene, in the positive electrode slurry, the lithium-containing graphene can coat the positive electrode active material, thereby preventing the positive electrode active material from binding with water and causing performance deterioration; at the same time, the solid content has good dispersibility in solvent water, has good processability, low cost, and is environmentally friendly.

[0061] In some embodiments, the lithium-containing graphene is at least partially coated on the surface of the positive electrode active material. This can form a hydrophilic layer on the surface of the positive electrode active material, improving the dispersibility of the positive electrode active material while preventing contact between the positive electrode active material and water. Furthermore, the lithium ions in the lithium-containing graphene can improve lithium ion transport within the positive electrode sheet, resulting in better kinetic performance for the secondary battery.

[0062] In some embodiments, the lithium-containing graphene includes lithium sulfonate-containing graphene. The sulfonic acid groups in the lithium sulfonate-containing graphene can further improve the dispersibility of the positive electrode active material in the positive electrode slurry through electrostatic repulsion, thereby improving the processability of the positive electrode slurry.

[0063] In some embodiments, the molar ratio of Li to S in the lithium sulfonate-containing graphene is 1:(1-10). Optionally, the molar ratio of Li to S in the lithium sulfonate-containing graphene is 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, or 1:10. Furthermore, the molar ratio of Li to S in the lithium sulfonate-containing graphene is 1:(1-5). When the molar ratio of Li to S in the lithium sulfonate-containing graphene is within the above range, the secondary battery prepared using the positive electrode slurry has better kinetic performance.

[0064] In some embodiments, the molar ratio of C to S in the lithium sulfonate-containing graphene is (3-12):1. Alternatively, the molar ratio of C to S in the lithium sulfonate-containing graphene is 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or 12:1. When the molar ratio of C to S in the lithium sulfonate-containing graphene is within the above range, the dispersibility of the solids in the positive electrode slurry is better.

[0065] The molar ratio of elements in the lithium sulfonate-containing graphene can be measured by methods known in the art. As an example, the molar ratio of elements in the lithium sulfonate-containing graphene in this application is measured using a Horiba 7021-H X-ray spectrometer.

[0066] In some embodiments, the mass percentage of lithium-containing graphene in the solid content is 0.01% to 2%. Alternatively, the mass percentage of lithium-containing graphene in the solid content can be within the range of any of the following values: 0.01%, 0.05%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, or 2%. Furthermore, the mass percentage of lithium-containing graphene in the solid content is 0.2% to 1.5%. A mass percentage of lithium-containing graphene within the above range can effectively improve the dispersibility of the positive electrode active material in the aqueous positive electrode slurry and prevent the positive electrode active material from deteriorating due to water absorption.

[0067] In some embodiments, the positive electrode active material includes LiFe m Mn 1-m PO4、Li(Ni x Co y Mn z Al a Cu b Zn c Ti d)O2, 0≤m≤1, x+y+z+a+b+c+d=1, 0.5≤x<1, 0.05≤y<1, 0≤z<0.5, 0≤a≤0.1, 0≤b≤0.1, 0≤c≤0.1, 0≤d≤0.1. Optionally, the positive electrode active material is LiFePO4.

[0068] In some embodiments, the solid inclusions further include a dispersant. Optionally, the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant. Optionally, the dispersant includes at least one of polyethyleneimine and polyethylene glycol octylphenyl ether. These dispersants synergize with the lithium-containing graphene to further improve the dispersibility of the positive electrode slurry. In particular, these dispersants interact with the sulfonic acid groups on the lithium-sulfonic acid-containing graphene, further improving dispersibility.

[0069] In some embodiments, the mass percentage of the dispersant in the solid content is 0.01% to 2%. Alternatively, the mass percentage of the dispersant in the solid content can be in a range consisting of any of the following values: 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.6%, or 2%. Furthermore, the mass percentage of the dispersant in the solid content is 0.1% to 0.5%. When the mass percentage of the dispersant is within the above range, the positive electrode slurry has good dispersibility and good processing performance.

[0070] In some embodiments, the solid content further includes an aqueous binder. Optionally, the aqueous binder includes at least one of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, and acrylonitrile-acrylic acid copolymer and its derivatives. The aqueous binder is soluble in water, and the positive electrode slurry has suitable viscosity and adhesiveness.

[0071] In some embodiments, the aqueous binder is an acrylonitrile-acrylic acid copolymer. Further, the acrylonitrile-acrylic acid copolymer has a number average molecular weight of 300,000 to 2,000,000.

[0072] In some embodiments, the mass percentage of the aqueous binder in the solid content is 0.1% to 5%. Alternatively, the mass percentage of the aqueous binder in the solid content can be within the range of any of the following values: 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, or 5%. Furthermore, the mass percentage of the aqueous binder in the solid content is 2% to 4%. When the mass percentage of the aqueous binder is within the above range, the positive electrode slurry has a suitable viscosity, which is conducive to the preparation of positive electrode sheets.

[0073] In some embodiments, the solid content further includes a conductive agent. Optionally, the conductive agent includes at least one of conductive carbon black, superconducting carbon black, conductive graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes.

[0074] In some embodiments, the weight percentage of the conductive agent in the solid inclusion is 0.1% to 5%. Alternatively, the weight percentage of the conductive agent in the solid inclusion can be within the range of any of the following values: 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, or 5%. Furthermore, the weight percentage of the conductive agent in the solid inclusion is 0.5% to 3%.

[0075] In some embodiments, the solid content of the positive electrode slurry is 40% to 90% by weight. Alternatively, the solid content of the positive electrode slurry is 50% to 70% by weight. The solid content in the positive electrode slurry is well dispersed, and the solid content can reach 90% by weight, further reducing the amount of solvent water used.

[0076] In some embodiments, the viscosity of the positive electrode slurry is 100 cp to 10,000 cp. Optionally, the viscosity of the positive electrode slurry is 3,000 cp to 7,000 cp. The viscosity of the positive electrode slurry within the above range is conducive to subsequent processing to prepare positive electrode sheets.

[0077] Another embodiment of the present application further provides a method for preparing the above-mentioned positive electrode slurry, comprising the following steps:

[0078] Mix the solids and water.

[0079] The positive electrode slurry preparation method is to mix the solid content containing the positive electrode active material and the lithium-containing graphene with water, so that the prepared positive electrode slurry has good dispersibility and processability, and the positive electrode active material is not easily deteriorated by water absorption.

[0080] In some embodiments, the step of mixing the solids and water comprises:

[0081] (1) The positive electrode active material, lithium-containing graphene, dispersant and conductive agent are mixed to prepare a pelletized material.

[0082] (2) Mixing the dough material, the aqueous binder and the water.

[0083] First, the positive electrode active material, lithium-containing graphene, dispersant and conductive agent are mixed to prepare a mass material, which can further improve the dispersibility of the positive electrode active material in the positive electrode slurry and avoid agglomeration or gelation.

[0084] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0085] In one embodiment of the present application, a secondary battery is provided.

[0086] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.

[0087] Positive electrode

[0088] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material. The positive electrode active material layer of the positive electrode sheet in the present application is prepared according to the positive electrode slurry of the first aspect.

[0089] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is provided on either or both of the two facing surfaces of the positive electrode current collector.

[0090] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate. The polymer material substrate includes substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0091] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. Alternatively, the positive electrode active material includes LiFe m Mn 1-m PO4、Li(Ni x Co y Mn z Al a Cu b Zn c Ti d)O2, 0≤m≤1, x+y+z+a+b+c+d=1, 0.5≤x<1, 0.05≤y<1, 0≤z<0.5, 0≤a≤0.1, 0≤b≤0.1, 0≤c≤0.1, 0≤d≤0.1. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0092] In some embodiments, the positive electrode active material layer further includes lithium-containing graphene. In some embodiments, the lithium-containing graphene is at least partially coated on the surface of the positive electrode active material. The lithium ions in the lithium-containing graphene can improve lithium ion transport in the positive electrode active material layer, thereby improving the kinetic performance of the secondary battery.

[0093] Furthermore, the lithium-containing graphene includes lithium sulfonate-containing graphene. In some embodiments, the molar ratio of the Li element to the S element in the lithium sulfonate-containing graphene is 1: (1 to 10). Optionally, the molar ratio of the Li element to the S element in the lithium sulfonate-containing graphene is 1: 1, 1: 2, 1: 3, 1: 4, 1: 5, 1: 6, 1: 7, 1: 8, 1: 9 or 1: 10. Further, the molar ratio of the Li element to the S element in the lithium sulfonate-containing graphene is 1: (1 to 5). When the molar ratio of the Li element to the S element in the lithium sulfonate-containing graphene is within the above range, the secondary battery kinetic performance is better. In some embodiments, the molar ratio of the C element to the S element in the lithium sulfonate-containing graphene is (3 to 12): 1. Optionally, the molar ratio of C to S in the lithium sulfonate-containing graphene is 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or 12:1. In some embodiments, in the positive electrode active material layer, the molar ratio of Li to S is (10-5000):1.

[0094] Specifically, the molar ratio of Li to S, or the molar ratio of C to S, in the lithium sulfonate-containing graphene or the positive electrode active material layer can be measured by methods known in the art. For example, it can be measured by SEM-EDS analysis using a ZEISS Sigma 300 scanning electron microscope and a Horiba 7021-H energy dispersive X-ray spectrometer.

[0095] In some embodiments, the mass percentage of lithium-containing graphene in the positive electrode active material layer is 0.01% to 2%. Alternatively, the mass percentage of lithium-containing graphene in the positive electrode active material layer can be within the range of any of the following values: 0.01%, 0.05%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, or 2%. Furthermore, the mass percentage of lithium-containing graphene in the positive electrode active material layer is 0.2% to 1.5%.

[0096] In some embodiments, the positive electrode active material layer may further include a dispersant. Optionally, the dispersant may include at least one of a cationic dispersant and an amphoteric dispersant. For example, the dispersant may include at least one of polyethyleneimine and polyethylene glycol octylphenyl ether.

[0097] In some embodiments, the mass percentage of the dispersant in the positive electrode active material layer is 0.01% to 2%. Alternatively, the mass percentage of the dispersant in the positive electrode active material layer can be in a range consisting of any of the following values: 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.6%, or 2%. Furthermore, the mass percentage of the dispersant in the positive electrode active material layer is 0.1% to 0.5%.

[0098] In some embodiments, the positive electrode active material layer optionally includes an aqueous binder. For example, the aqueous binder may include at least one of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, and acrylonitrile-acrylic acid copolymer and its derivatives. In some embodiments, the aqueous binder is acrylonitrile-acrylic acid copolymer. Furthermore, the acrylonitrile-acrylic acid copolymer has a number average molecular weight of 300,000 to 2,000,000.

[0099] In some embodiments, the mass percentage of the aqueous binder in the positive electrode active material layer is 0.1% to 5%. Alternatively, the mass percentage of the aqueous binder in the positive electrode active material layer can be within the range of any of the following values: 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, or 5%. Furthermore, the mass percentage of the aqueous binder in the positive electrode active material layer is 2% to 4%.

[0100] In some embodiments, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of conductive carbon black, superconducting carbon black, conductive graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes. In some embodiments, in the positive electrode active material layer, the mass percentage of the conductive agent is 0.1% to 5%. Optionally, in the positive electrode active material layer, the mass percentage of the conductive agent may be in the range of any of the following values: 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, or 5%. Furthermore, in the positive electrode active material layer, the mass percentage of the conductive agent is 0.5% to 3%.

[0101] In some embodiments, the positive electrode sheet can be prepared by the following method: the above-mentioned positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0102] Negative electrode

[0103] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0104] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is provided on either or both of the two facing surfaces of the negative electrode current collector.

[0105] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer base material. The polymer base material includes base materials such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0106] In some of the embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0107] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0108] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0109] In some embodiments, the negative electrode active material layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0110] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0111] electrolytes

[0112] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0113] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0114] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0115] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0116] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0117] Isolation film

[0118] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0119] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0120] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0121] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0122] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0123] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 with a square structure as an example.

[0124] In some embodiments, referring to FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and side plates connected to the bottom plate, and the bottom plate and the side plates enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0125] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain one or more secondary batteries. The specific number may be selected by those skilled in the art based on the application and capacity of the battery module.

[0126] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0127] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0128] In some embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. The specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0129] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0130] In addition, the present application also provides an electrical device, which includes at least one of the secondary batteries, battery modules, or battery packs provided in the present application. The secondary batteries, battery modules, or battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device may include, but is not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0131] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0132] Figure 6 shows an example of an electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the electric device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.

[0133] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0134] Example

[0135] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0136] Example 1:

[0137] Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate (LFP), lithium sulfonate graphene, conductive agent, and dispersant are kneaded evenly in a weight ratio of 96.5:0.2:1:0.3, and then the mixed kneaded mass of the positive electrode active material lithium iron phosphate, lithium sulfonate graphene, conductive agent, dispersant, and aqueous binder are kneaded in a weight ratio of 98:2, wherein the molar ratio of Li / S of the lithium sulfonate graphene is 1:1, and the molar ratio of C / S is 6:1, polyethyleneimine is used as the dispersant, and LA-133 type aqueous binder is used as the aqueous binder; the remainder is stirred and mixed evenly with solvent deionized water to obtain a positive electrode slurry with a solid content of 50%; then the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, and then dried, cold pressed, and cut to obtain the positive electrode sheet.

[0138] Preparation of negative electrode sheets: The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dispersed in the solvent deionized water in a mass ratio of 96.2:0.8:0.8:1.2, and the mixture is evenly mixed to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and the negative electrode sheets are obtained after drying, cold pressing, and slitting.

[0139] Preparation of electrolyte: In an argon atmosphere glove box (H2O <0.1ppm, O2 <0.1ppm), organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7, 12.5% ​​LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred to obtain an electrolyte.

[0140] Isolation film: Polypropylene film is used as the isolation film.

[0141] Secondary battery preparation: The positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide insulation. The cells are then wound to form a bare cell. The tabs are welded to the bare cell, which is then encased in an aluminum shell and baked at 80°C to remove moisture. The electrolyte is then injected and sealed to produce a dead battery. The dead battery then undergoes a series of processes, including resting, hot and cold pressing, formation, shaping, and capacity testing, to produce a secondary battery product.

[0142] Examples 2 to 6:

[0143] The difference between Examples 2 to 6 and Example 1 is that the amount of lithium sulfonate-containing graphene in the positive electrode slurry is different.

[0144] Examples 7-8:

[0145] The difference between Examples 7 and 8 and Example 1 is that the C / S molar ratio of the lithium sulfonate-containing graphene in the positive electrode slurry is different.

[0146] Examples 9-11:

[0147] The difference between Examples 9 to 11 and Example 1 is that the Li / S molar ratio of the lithium sulfonate-containing graphene in the positive electrode slurry is different.

[0148] Examples 12 to 16:

[0149] The difference between Examples 12 to 16 and Example 1 is that the amount of dispersant used in the positive electrode slurry is different.

[0150] Examples 17 to 19:

[0151] The difference between Examples 17 to 19 and Example 1 is that the amount of the aqueous binder in the positive electrode slurry is different.

[0152] Example 20:

[0153] The difference between Example 20 and Example 1 is that the dispersant in the positive electrode slurry is polyethylene glycol octylphenyl ether.

[0154] Example 21:

[0155] The difference between Example 21 and Example 1 is that the aqueous binder in the positive electrode slurry is sodium alginate.

[0156] Example 22:

[0157] The difference between Example 22 and Example 1 is that the positive electrode active material in the positive electrode slurry is LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811).

[0158] Comparative Example 1:

[0159] The difference between Comparative Example 1 and Example 1 is that the positive electrode slurry does not contain lithium-containing graphene and dispersant.

[0160] Comparative Example 2:

[0161] The difference between Comparative Example 2 and Example 1 is that the positive electrode slurry does not contain lithium-containing graphene.

[0162] The lithium sulfonate graphene used in the above embodiments can be obtained through commercial channels or prepared in a suitable manner known to those skilled in the art. As an example, the preparation method of lithium sulfonate graphene is as follows: sulfonate graphene is uniformly dispersed in DMF, lithium hydroxide is then added and stirred for 1 to 4 hours, and dried at 100°C to 120°C to obtain lithium sulfonate graphene. The type of sulfonate graphene and the amount of sulfonate graphene and lithium hydroxide are adjusted according to the element molar ratio in Table 1. The elemental composition of the lithium sulfonate graphene prepared above can also be obtained by testing with a Horiba 7021-H X-ray spectrometer to obtain the C / S molar ratio and Li / S molar ratio of the lithium sulfonate graphene.

[0163] The compositions of the positive electrode slurries of Examples 1 to 22 and Comparative Examples 1 to 2 are recorded in Table 1.

[0164] Test part:

[0165] Cathode slurry particle size test:

[0166] The prepared positive electrode slurry was allowed to stand for 10 minutes, and an appropriate amount of the positive electrode slurry was added to 20 ml of deionized water (concentration to ensure 8%-12% shading), and ultrasonically treated for 5 minutes (53KHz / 120W) to completely disperse it as the sample to be tested; the Dv50 particle size of the sample to be tested was measured using a Malvern 2000 (MasterSizer 2000) laser particle size analyzer according to the standard procedure GB / T19077-2016 / ISO 13320:2009.

[0167] Secondary battery initial gram capacity test:

[0168] Taking Example 1 as an example, at 25°C, the secondary battery was charged at a constant current of 1 / 3C to 3.65V (4.25V for NCM811), then charged at a constant voltage of 3.65V (4.25V for NCM811) to a current of 0.05C, left for 5 minutes, and then discharged at 1 / 3C to 2.5V (2.8V for NCM811). The resulting capacity was divided by the mass of the positive electrode active material in the positive electrode and recorded as the initial gram capacity Cw.

[0169] DC impedance test:

[0170] Taking Example 1 as an example, the secondary battery is charged to 3.65V (4.25V for NCM811) at a constant current of 1.5C, and then charged to 0.05C at a constant voltage. Let it stand for 30 minutes; discharge at a current of 0.1C for 10s (take a point once every 0.1s and record the corresponding voltage value U1), and discharge at a current of 1C for 360s (take a point once every 0.1s and record the corresponding voltage value U2). Repeat the charge and discharge steps 5 times. "1C" is the current value that completely discharges the battery capacity within 1 hour. The DCR is calculated according to the following formula: R = (U2-U1) / (1C-0.1C). The DCR described in this application is the value at 50% SOC (state of charge).

[0171] High rate current cycling performance test:

[0172] Taking Example 1 as an example, at 25°C, the secondary battery was charged at a constant current of 25C to 3.65V (4.25V for NCM811), then charged at a constant voltage of 3.65V (4.25V for NCM811) to a current of 0.05C, left for 5 minutes, and then discharged at 25C to 2.5V (2.8V for NCM811). The initial DC resistance R0 was recorded. The above steps were repeated for the same battery, and the DC resistance Rn of the battery after the nth cycle was recorded. The battery DCR growth rate after each cycle is Pn = Rn / R0*100%-1. During this test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, and so on. The 100th cycle corresponds to n=100. The secondary battery DCR growth rate data in Table 2 is the data measured after 100 cycles under the above test conditions, that is, the value of P100.

[0173] The electrochemical performance test data of the secondary batteries of Examples 1 to 22 and Comparative Examples 1 to 2 are recorded in Table 2.

[0174] Table 1 Composition of positive electrode slurries of Examples 1 to 22 and Comparative Examples 1 to 2

[0175]

[0176]

[0177] Note: The mass contents in Table 1 all represent the mass content of the substances in the solid content of the positive electrode slurry.

[0178] Table 2 Electrochemical properties of secondary batteries of Examples 1 to 22 and Comparative Examples 1 to 2

[0179]

[0180]

[0181] It can be seen from the relevant data in Table 1 and Table 2 that the positive electrode slurries of Comparative Examples 1 and 2 do not contain lithium-containing graphene, the Dv50 particle size of the positive electrode slurries is 1.37 μm to 1.51 μm, the initial gram capacity of the secondary batteries of Comparative Examples 1 and 2 is 156 mAh / g, the DCR is 1.58Ω to 1.75Ω, and the DCR growth rate after 100 cycles at 25C is 27% to 29%.

[0182] Compared with Comparative Examples 1-2, the positive electrode slurries of Examples 1-21 contain lithium-containing graphene, and the Dv50 particle size of the positive electrode slurries is 1.07 μm to 1.33 μm, indicating good dispersibility. The initial gram capacity of the secondary batteries of Examples 1-21 is 158 mAh / g to 160 mAh / g, which is higher than that of the secondary batteries of Comparative Examples 1-2. This indicates that during the preparation process of the secondary batteries of Examples 1-22, the lithium iron phosphate is not easily degraded by water absorption, resulting in a decrease in capacity. In addition, the DCR of the secondary batteries of Examples 1-21 is 1.38 Ω to 1.67 Ω, and the DCR growth rate after 100 cycles at 25C is 11% to 23%. The lithium ions in the lithium-containing graphene can improve the lithium ion transport of the secondary battery, thereby reducing the DCR. The lithium-containing graphene is at least partially coated on the surface of the positive electrode active material, resulting in the secondary battery having good cycle performance and is not easily degraded by high-rate charge and discharge. Among them, the binder content in Example 21 is low, and the electrode bonding strength is slightly lower than the positive electrode sheets of Examples 1 to 20, so the DCR is higher and the DCR increases more during high-rate charge and discharge.

[0183] In the secondary battery of Example 22, the positive electrode active material is NCM811, the Dv50 particle size of the positive electrode slurry is 4.70 μm, and the dispersion of the positive electrode slurry is good; the initial gram capacity of the secondary battery is 174 mAh / g, the DCR is 1.37 Ω, and the DCR growth rate after 100 cycles at 25C is 11%, which has good kinetic performance and cycle performance.

[0184] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0185] The above-described embodiments merely represent several implementation methods of the present application. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art could make various modifications and improvements without departing from the spirit of the present application, all of which fall within the scope of protection of the present application. Therefore, the scope of protection of the present patent application shall be determined by the appended claims.

Claims

1. A positive electrode slurry, characterized in that: Includes solids and water; The solid content includes a positive electrode active material capable of inserting and extracting lithium ions and lithium-containing graphene.

2. The positive electrode slurry according to claim 1, characterized in that The lithium-containing graphene is at least partially coated on the surface of the positive electrode active material.

3. The positive electrode slurry according to claim 1 or 2, characterized in that The lithium-containing graphene includes lithium-sulfonate-containing graphene.

4. The positive electrode slurry according to claim 3, characterized in that The molar ratio of Li element to S element in the lithium sulfonate-containing graphene is 1:(1-10); Optionally, the molar ratio of Li element to S element in the lithium sulfonate-containing graphene is 1:(1-5).

5. The positive electrode slurry according to claim 3 or 4, characterized in that The molar ratio of the C element to the S element in the lithium sulfonate-containing graphene is (3-12):

1.

6. The positive electrode slurry according to any one of claims 1 to 5, characterized in that: In the solid content, the mass percentage of the lithium-containing graphene is 0.01% to 2%; Optionally, in the solid content, the mass percentage of the lithium-containing graphene is 0.2% to 1.5%.

7. The positive electrode slurry according to any one of claims 1 to 6, characterized in that: The positive electrode active material includes LiFe m Mn 1-m PO4、Li(Ni x Co y Mn z Al a Cu b Zn c Ti d ) at least one of O2, 0≤m≤1, x+y+z+a+b+c+d=1, 0.5≤x<1, 0.05≤y<1, 0≤z<0.5, 0≤a≤0.1, 0≤b≤0.1, 0≤c≤0.1, 0≤d≤0.1; Optionally, the positive electrode active material is LiFePO4.

8. The positive electrode slurry according to any one of claims 1 to 7, characterized in that: The solid content also includes a dispersant; Optionally, the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant; Optionally, the dispersant includes at least one of polyethyleneimine and polyethylene glycol octylphenyl ether.

9. The positive electrode slurry according to claim 8, characterized in that In the solid content, the mass percentage of the dispersant is 0.01% to 2%; Optionally, in the solid content, the mass percentage of the dispersant is 0.1% to 0.5%.

10. The positive electrode slurry according to any one of claims 1 to 9, characterized in that: The solid content also includes an aqueous binder; Optionally, the aqueous binder includes at least one of methyl cellulose and salts thereof, xanthan gum and salts thereof, chitosan and salts thereof, alginic acid and salts thereof, polyacrylamide, acrylonitrile-acrylic acid copolymer and derivatives thereof.

11. The positive electrode slurry according to claim 10, characterized in that The aqueous binder is acrylonitrile-acrylic acid copolymer; Optionally, the number average molecular weight of the acrylonitrile-acrylic acid copolymer is 300,000 to 2,000,000.

12. The positive electrode slurry according to claim 10 or 11, characterized in that: In the solid content, the mass percentage of the aqueous binder is 0.1% to 5%; Optionally, in the solid content, the mass percentage of the aqueous binder is 2% to 4%.

13. The positive electrode slurry according to any one of claims 1 to 12, characterized in that: The solid content also includes a conductive agent; Optionally, the conductive agent includes at least one of conductive carbon black, superconducting carbon black, conductive graphite, acetylene black, Ketjen black, graphene and carbon nanotubes.

14. The positive electrode slurry according to claim 13, characterized in that In the solid content, the mass percentage of the conductive agent is 0.1% to 5%; Optionally, in the solid content, the mass percentage of the conductive agent is 0.5% to 3%.

15. The positive electrode slurry according to any one of claims 1 to 14, characterized in that: In the positive electrode slurry, the mass percentage of the solid content is 40% to 90%; Optionally, in the positive electrode slurry, the mass percentage of the solid content is 50% to 70%.

16. The positive electrode slurry according to any one of claims 1 to 15, characterized in that: The viscosity of the positive electrode slurry is 100 cp to 10000 cp; Optionally, the viscosity of the positive electrode slurry is 3000cp to 7000cp.

17. The method for preparing the positive electrode slurry according to any one of claims 1 to 16, characterized in that: The following steps are involved: The solid content and the water are mixed.

18. The method for preparing the positive electrode slurry according to claim 17, wherein: The step of mixing the solid content and the hydrophilic solvent comprises: Mixing the positive electrode active material, lithium-containing graphene, a dispersant, and a conductive agent to prepare a pelletized material; The dough material, aqueous binder and water are mixed.

19. A positive electrode plate, characterized in that: include: positive electrode current collector; and A positive electrode active material layer is provided on at least one surface of the positive electrode current collector; the positive electrode active material layer is made from the positive electrode slurry according to any one of claims 1 to 16.

20. The positive electrode sheet according to claim 19, characterized in that: The positive electrode active material layer includes graphene containing lithium sulfonic acid groups; Optionally, in the positive electrode active material layer, the molar ratio of Li element to S element is (10-5000):

1.

21. A method for preparing a positive electrode sheet, characterized in that: The following steps are involved: A positive electrode active material layer is prepared on at least one surface of a positive electrode current collector using a positive electrode slurry; the positive electrode slurry is the positive electrode slurry according to any one of claims 1 to 16.

22. A secondary battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to claim 19 or 20 or a positive electrode sheet prepared by the method for preparing the positive electrode sheet according to claim 21.

23. A battery module, characterized in that: Includes the secondary battery according to claim 22.

24. A battery pack, characterized in that: A battery module comprising the battery module of claim 23.

25. An electrical device, characterized in that: The battery comprises at least one selected from the group consisting of the secondary battery according to claim 22, the battery module according to claim 23, and the battery pack according to claim 24.

Citation Information

Patent Citations

  • Carbon material used for lithium battery and preparation method for carbon material

    CN106935854A

  • Preparation methods for dry-process and wet-process carbon-coated high-nickel ternary positive electrode materials

    CN109390579A

  • Graphene-coated lithium ion battery ternary positive electrode material

    CN110311136A

  • Lithium sulfonate substituted fluorinated graphene as well as preparation method and application thereof

    CN110350154A